Effectiveness of Web-Based Nutrition Education for Chronic Kidney Disease Patients - Suyanee Pongthananikorn; Jitprasong Lamsaard; Tippawan Siritientong (Journal of Pharmacy and Nutrition Sciences, 2018)
Background: In the early stages of chronic kidney disease (CKD), encouraging health behaviors can help prevent the progression of kidney disease leading to eventual kidney failure. The studies of health education using computer technology have been greatly developed, especially web-based nutrition education. Objective: To determine the effectiveness of a nutrition education website for CKD patients. Method: The design of this quasi-experimental research was a group pre-test/post-test. The participants were pre-dialysis CKD patients who were enrolled on the developed website www.banraktai.com. The participants were required to complete an eating behavior questionnaire and knowledge test. They accessed the website for eight weeks, and at week 8, they completed the eating behavior questionnaire and knowledge test again. The main outcomes were the changes in scores of nutrition knowledge and eating behavior that were compared between the baseline and after the intervention using the paired t-test. The correlation between nutrition knowledge scores and eating behavior scores was determined using Spearman’s correlation coefficient. Results: There were 44 participants that completed the study. The results showed that the participants had significant improvement in both knowledge scores and consumption behavior scores (p < 0.001 and p = 0.041, respectively). However, there was no correlation between the nutrition knowledge scores and the eating behavior scores. Conclusions: Web-based nutrition education can improve knowledge scores but is not effective enough to encourage and motivate CKD patients to make eating behavior changes.